The Impact of Defaults on Technology Adoption, and its Underappreciation by Policymakers - Peter Leopold S. Bergman; Todd Rogers (Center for Economic Studies and ifo Institute (CESifo), 2017)
We conduct an experiment to understand how enrollment defaults affect the take up and impact of an education technology. We show that a standard and simplified opt-in process induce low take up. Automatically enrolling parents increases adoption significantly and improves student achievement. Our surveys show automatic enrollment is uncommon because its impact is underestimated: District leaders overestimate take-up under the standard condition by 38 percentage points and underestimate take-up under automatic enrollment by 31 percentage points. After learning the actual take-up rates, there is a 140% increase in willingness to pay for the technology when shifting implementation to automatic enrollment.
Keywords: I21; 330; adoption; defaults; technology